Avaliação do perfil motivacional de estudantes de medicina de duas instituições com métodos de ensino diferentes – Estudo transversal, 2018 - CADÊTE FILHO, A. A (2019)
Motivation is a fundamental component of any reliable model of human performance and can be defined as a need or desire linked to the will to achieve an expected goal. Two basic types of motivation are characterized: intrinsic motivation, in which something is done for the interest and pleasure inherent in action; and extrinsic motivation, in which something is done because of consequence or distinct outcome of the action. With this, the line of motivational studies related to university learning, and more specifically, medical, has gained prominence. In this motivational context, the influence of teaching methodology should be emphasized. The study emphasizes that students who perceive themselves as autonomous in their academic interactions have positive results regarding motivation and the perception of competence. The dissertation aimed to evaluate the motivation to learn from students of the 4th year of medicine and its correlation with the curricular model (PBL and traditional) and sociodemographic factors. It was a cross-sectional and quantitative study that was conducted through a self-administered questionnaire containing sociodemographic questions and the Academic Motivation Scale (EMA) to assess the motivation of medical students. The target population consisted of 147 students from the 4th year of medicine from two schools with different methods: 73 students from Institution A (PBL) and 74 students from the Institution B (traditional). The fourth year of medical education was considered, since it is the transition period of the medical course, with the deepening for the professional and for the practical activities. Until this moment of the course, the two institutions present differences in the methodologies, whereas in the traditional one there is a more robust passage of theoretical activities for the practices in comparison with the PBL, that begins in the practice from the first periods of the course. The beginning of the boarding schools favors the students a greater active clinical practice in both institutions. In the study we observed that, in the 4th year students of both institutions, the intrinsic motivation was greater than the extrinsic motivation. Our results also showed that Institution A students (PBL method) had higher mean scores, both in intrinsic and extrinsic motivation. It was observed that the variables female gender, age group less than 23 years old, living alone, having done all the same in the same institution and having a health problem had a positive influence on the motivation of the students. The 147 students were divided into two distinct motivational profiles, and the group with the highest degree of motivation was predominantly female students living alone and the Institution A. The results suggest that the higher degree of academic motivation may be related to the PBL curriculum model, as well as the variables gender and dwelling alone. More literature and investigations are necessary to understand the importance of these factors, along the course, in the motivation profile of medical students